Evaluation of capacity-building strategies for mental health system strengthening in low- and middle-income countries for service users and caregivers, policymakers and planners, and researchers - Sara Evans-Lacko; Charlotte Hanlon; Atalay Alem; Jose Luis Ayuso-Mateos; Dan Chisholm; Oye Gureje; Mark Jordans; Fred Kigozi; Heidi Lempp; Crick Lund; Inge Petersen; Rahul Shidhaye; et al. (BJPsych Open, 2019)
BackgroundStrengthening of mental health systems in low- and middle-income countries (LMICs) requires the involvement of appropriately skilled and committed individuals from a range of stakeholder groups. Currently, few evidence-based capacity-building activities and materials are available to enable and sustain comprehensive improvements.AimsWithin the Emerald project, the goal of this study was to evaluate capacity-building activities for three target groups: (a) service users with mental health conditions and their caregivers; (b) policymakers and planners; and (c) mental health researchers.MethodWe developed and tailored three short courses (between 1 and 5 days long). We then implemented and evaluated these short courses on 24 different occasions. We assessed satisfaction among 527 course participants as well as pre–post changes in knowledge in six LMICs (Ethiopia, India, Nepal, Nigeria, South Africa, Uganda). Changes in research capacity of partner Emerald institutions was also assessed through monitoring of academic outputs of participating researchers and students and via anonymous surveys.ResultsShort courses were associated with high levels of satisfaction and led to improvements in knowledge across target groups. In relation to institutional capacity building, all partner institutions reported improvements in research capacity for most aspects of mental health system strengthening and global mental health, and many of these positive changes were attributed to the Emerald programme. In terms of outputs, eight PhD students submitted a total of 10 papers relating to their PhD work (range 0–4) and were involved in 14 grant applications, of which 43% (n = 6) were successful.ConclusionsThe Emerald project has shown that building capacity of key stakeholders in mental health system strengthening is possible. However, the starting point and appropriate strategies for this may vary across different countries, depending on the local context, needs and resources.Declaration of interestS.E.L. received consulting fees from Lundbeck.